Answered

Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

solve for x 27^(2x+4)=1/9^(x-46)

Sagot :

naǫ
[tex]27^{2x+4}=(\frac{1}{9})^{x-46} \\ (3^3)^{2x+4}=(3^{-2})^{x-46} \\ 3^{3(2x+4)}=3^{-2(x-46)} \\ 3^{6x+12}=3^{-2x+92} \\ 6x+12=-2x+92 \\ 6x+2x=92-12 \\ 8x=80 \\ x=10[/tex]